Doing Middle Leadership Right : a practical guide to leading with honesty and integrity in schools - Bawden, Lyndsay; Macis-Riley, Kaley; Hickin, Jade (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Are you a new or aspiring middle leader? Or have you been doing the job for a while but want some practical tips to ease workload and support your staff? This book draws together real experiences of middle leadership, both good and bad, and offers practical tips to help you find your voice, support your team, act with integrity, and work with the Senior Leadership Team to improve your school. Covering all aspects of middle leadership including leadership styles, pedagogical approaches, the role of social media, how to tackle difficult conversations, staff wellbeing and much more, the authors will help you avoid common pitfalls, navigate highs and lows, and develop a school environment that enables both students and staff to flourish. For any new, experienced, or prospective middle-leader, Doing Middle Leadership Right provides a professional insight into how to lead with humanity at the centre of your practice. It puts staff and their wellbeing first - focussing on how to have the highest standards for both students and staff, but also how to lead ethically"--
Introduction -- Ethical leadership and managing change -- Balancing accountability and humanity -- Difficult conversations -- Curriculum development, the theory -- Curriculum development, the practicalities -- Teaching and learning -- Information classification: general -- Assessment -- Teaching to the top -- Behaviour management -- CPD and coaching -- Social media -- Flexible working -- Positive disruption -- Common pitfalls, and debunking myths -- Conclusion.
Includes bibliographical references and index.
Keywords: Educational leadership -- Moral and ethical aspects; School management and organization -- Moral and ethical aspects; Middle managers -- In-service training